2022
DOI: 10.1016/j.chb.2022.107218
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence that brief exposure to vaccination-related internet memes may influence intentions to vaccinate against COVID-19

Abstract: Despite global efforts to rapidly distribute COVID-19 vaccines, early estimates suggested that 29–35% of the population were hesitant/unwilling to receive them. Countering such vaccine hesitancy is thus an important priority. Across two sets of online studies (total n = 1584) conducted in the UK before (August–October 2020) and immediately after the first effective vaccine was publicly announced (November 10–19, 2020), brief exposure (<1 min) to vaccination memes boosted the potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…As noted earlier, targeting messages to a sub-population group’s identity and using social connection features to foster interactions among participants increased the participants’ engagement in the content. Moreover, the use of visual aids is pertinent to immunization campaigns because visual aids are processed faster, receive selective attention, and are retained longer in memory than texts ( Geniole et al, 2022 , Peterson et al, 2017 ). Visual aids are, therefore, persuasive among those with lower digital literacy and a high level of vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, targeting messages to a sub-population group’s identity and using social connection features to foster interactions among participants increased the participants’ engagement in the content. Moreover, the use of visual aids is pertinent to immunization campaigns because visual aids are processed faster, receive selective attention, and are retained longer in memory than texts ( Geniole et al, 2022 , Peterson et al, 2017 ). Visual aids are, therefore, persuasive among those with lower digital literacy and a high level of vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…The present study broadens research on memes' relationships with health behaviors. Whereas previous research studied memes alluding to the pandemic (Myrick et al., 2022) or actively encouraging certain health behaviors (Geniole et al., 2022), we examined memes that downplay the pandemic's severity and question the need for such behaviors. Supporting our hypotheses; COVID‐19 disparagement memes signaled a local norm of tolerance for unsafe pandemic behaviors, which permitted people viewing COVID‐19 as nonthreatening to forego the protocols set by the larger society.…”
Section: Discussionmentioning
confidence: 99%
“…Like any major event in modern times, COVID‐19 spawned thousands of humorous memes. Several studies on COVID‐19 demonstrate how coping and health behaviors are related to exposure to memes themed around the oddities of living during a pandemic (Myrick et al., 2022; Torres‐Marín et al., 2022) and memes mocking anti‐vaccination communities and COVID‐19 skeptics (Geniole et al., 2022). However, no studies have investigated the impact of memes that mock and downplay the pandemic, such as humor common among skeptic communities (Scannell et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Our Study 1 data analysis also revealed that survey respondents relied heavily on social media to get trustworthy vaccine information. To explore the kind of meme‐based vaccine messaging available to an average Twitter audience in the United States, we constructed Study 2 as an Exploratory analysis of anti‐vaccine memes circulating on social media during the data collection timeframe of Study 1 (Geniole et al, 2022).…”
Section: Studymentioning
confidence: 99%